Theorizing International Politics of Research, Science, and Technology: Implications for Global Governance, National Security, and Economic Growth - Julius Adinoyi (International Studies Journal)
This article examines the value of understanding the international politics surrounding research, science and technology (RST) in today‟s world.It encompasses intricate connections between nations, international organizations, and multinational enterprises,which is essential for economic growth, social development, and national security.The significance of elements like anarchy, capitalism, welfare, and security that influences the global politics of RST is highlighted in the essay.In order to counteract technology misuse, the authors stress the significance of establishing ethical standards. Those standardsdirect the creation and use of technology and a critical appreciation of the ideologies and values that support such development and use.This paper also emphasizes the crucial role that research, and the network of knowledge-based specialists play in determining policy results.Scientific data and expert opinion frequently influence these results.With examples from nations like the U.K., U.S., Japan, Russia, China, South Korea, Kenya and Nigeria, the impact of organizational and technological innovation on establishing and falling hegemonic powers is addressed.The article concludes by emphasizing the crucial role that the international politics of RST plays for academics and decision[1]makers, with implications for national security, global governance, and economic growth.